E-062 Comparison of FRED and PED in the treatment of intracerebral aneurysms. (23rd July 2022) - El Naamani, K; Saad, H; Chen, C; Abbas, R; Sioutas, G; Amllay, A; Yudkoff, C; Carreras, A; Sambangi, A; Hunt, A; Jain, P; Dougherty, J; et al.
Abstract : Objectives: Compare the outcomes of pipeline embolization device (PED; Medtronic Inc, Dublin, Ireland) and Flow-Redirection Endoluminal device (FRED; MicroVention, Aliso Viejo, California) in the treatment of intracranial aneurysms. Methods: This is a single- center retrospective review of aneurysms treated with PED and FRED devices. Patients treated with PED or FRED were included. Cases requiring multiple or adjunctive devices were excluded. Primary outcome was complete aneurysm occlusion at 6 months. Secondary outcomes included good functional outcome, need for retreatment, any complication. Results: The study cohort comprised 150 patients including 35 aneurysms treated with FRED, and 115 treated with PED. Mean neck diameter was significantly higher in the FRED cohort (2.3 mm vs 1.9 mm, p=0.043). Aneurysm characteristics including location and size were comparable between the two cohorts. 6-month complete occlusion rate was significantly higher in the PED cohort (74.7% vs. 51.5%; OR=0.36 [0.156–0.83], p=0.017) but lost significance after inverse probability weights (IPW). Patients in the PED cohort were associated with higher rates of periprocedural complications, and the rate of in-stent stenosis was approximately double in the FRED cohort (15.2% vs. 6.9%; OR=2.411 [0.682–8.518], p=0.172). Conclusion: Compared to PED, FRED offers modest 6 months occlusion rates which may be due to aneurysmal and baseline patient characteristics differences between both cohorts. Though not significant, FRED was associated with a higher complication rate mostly due to in-stent stenosis. Additional studies with longer follow-up durations should be conducted to further evaluate FRED thrombogenicity and efficacy compared to other flow diverters. Disclosures: K. El Naamani: None. H. Saad: None. C. Chen: None. R. Abbas: None. G. Sioutas: None. A. Amllay: None. C. Yudkoff: None. A. Carreras: None. A. Sambangi: None. A. Hunt: None. P. Jain: None. J. Dougherty: None. S. Tjoumakaris: 2; C; Medtronic, Microvention. M. Gooch: 2; C; Stryker. N. Herial: None. R. Rosenwasser: None. H. Zarzour: None. R. Schmidt: None. P. Jabbour: 2; C; Medtronic, Microvention, Balt, Cerus Endovascular.